Pengaruh Sanitasi Lingkungan Terhadap Kejadian Stunting Pada Balita - Mona Rahayu Putri; Trisna Yuni Handayani; Desi Pramita Sari (JURNAL KESEHATAN MERCUSUAR, 2022)
Toddlers are a group of individuals who are vulnerable to nutrition. Nutritional problems can have a serious impact on the quality of human resources. Nutritional problems are growth failure in early life, one of which is stunting. The prevalence of stunting under five in Indonesia in 2005-2017 was 36.4%. Stunting toddlers in the future will have difficulty in achieving optimal physical and cognitive development. One of the factors that influence the incidence of stunting in baita is environmental sanitation. This study aims to determine the effect of environmental sanitation on the incidence of stunting. This research is a quantitative research, descriptive analytic research type with a cross sectional approach. The sampling technique is purposive sampling. The sample in this study were mothers who had toddlers in the hiterland area of ​​Batam City which had 96 toddlers who were adjusted to the inclusion criteria. Data analysis using chi square. The result of this research is that there is an effect of environmental sanitation on the incidence of stunting in children under five (P value 0.009). Conclusion unhealthy environmental sanitation can affect the incidence of stunting in toddlers. There needs to be cooperation with various related parties to provide health education and improve environmental sanitation, especially in remote areas